THEORETICAL-METHODOLOGICAL NOTES TO THE ANALYSIS OF THE DEGRADATION OF LABOR IN THE CONTEXT OF ELECTRICITY PRODUCTION IN THE AMAZON - Alves, Jose; Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
Brazil fits into the temporality of structural crisis of capital in this beginning of the XXI century, experiencing an intense reorganization of national capitalism, called New Developmentalism. Among the State strategies is the resumption of planning in governments of Luiz Inacio Lula da Silva and Dilma Rousseff, being PAC the articulator program, as in the case of energy infrastructure policy. It is at this conjuncture that Amazon reinstates itself as the new hydropower frontier from the commodification of nature (hydric bodies) in areas of hydrobusiness-energy, such as hydroelectric power plants of Jirau and Santo Antonio, in the Madeira (RO) hydroelectric complex. This issue is addressed in the article, which presents theoretical and methodological reflections and notes for the analysis of the degradation and overexploitation of labour in the industry of electric power production in the Amazon.
Keywords: Amazon; labour; Jirau Hydroelectric Power Plant